(untitled) (Bangladesh Journal of Microbiology, 2010)
The phenol and monochlorophenols-degrading bacteria were isolated from the soil samples adjacent to textile, pharmaceuticals, industries and automobile workshops. Twenty seven isolates were recovered including twelve phenol, four 2-chlorophenol (2-CP) and eleven 4-chlorophenol (4-CP) degrading organisms. Among them five isolates were chosen as potential monochlorophenol-degrader; four of them were identified as species of Pseudomonas and one as Aeromonas. The biodegradability of phenol and monochlorophenol followed the order: phenol > 4-chlorophenol > 2-chlorophenol. Pseudomonas sp. AP2, Pseudomonas sp. AP3, Pseudomonas sp. AP4 and Aeromonas sp. PP3 degraded 400 and 600 ppm phenol within 48 and 72 h, and Pseudomonas sp. A4-CP2 degraded 600 and 800 ppm phenol in 48 and 72 h respectively. Pseudomonas sp. A4-CP2 also degraded 200 ppm 2-chlorophenol within 96 h and 200 and 350 ppm 4-chlorophenol within 48 and 75 h respectively. Bacterial isolates grew well in liquid culture containing 600 ppm phenol, while the growth was scanty in the medium containing 400 or 800 ppm phenol, except for Pseudomonas sp. A4CP2. The isolate Pseudomonas sp. A4CP2 also grew on 2-CP and 4-CP at concentrations of 200 and 350 ppm respectively. The correlation coefficient (at 0.01 level of significance) between bacterial growth and degradation capability of the isolates AP2, AP3, AP4, A4CP2 and PP3 were -0.835**, -0.847**, -0.700**, -0.946** and -0.401 respectively. Keywords: Biodegradation; Phenol; 2-Chlorophenol; 4-Chlorophenol; Pseudomonas; Aeromonas DOI: http://dx.doi.org/10.3329/bjm.v25i1.4854 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 41-44